Wonder - Hoberman, David, 1953-; Lieberman, Todd.; Chbosky, Stephen; Tremblay, Jacob; Roberts, Julia, 1967-; Wilson, Owen, 1968-; Patinkin, Mandy; Diggs, Daveed; Palacio, R. J.; Lions Gate Films; Participant Media; Walden Media; et al. (Santa Monica, CA : Lions Gate Entertainment, 2018)
Based on the New York best seller, this tells the incredibly inspiring and heartwarming story of August Pullman, a boy with facial differences who enters fifth grade, attending a mainstream elementary school for the first time.
Based on the novel by R.J. Palacio.
Originally released as a motion picture in 2017.
Special features: Audio commentary with Stephen Chbosky and R.J. Palacio ; Brand new eyes music video; Wonder soundtrack behind-the-scenes featurette; trailers.
Director of photography, Don Burgess ; editor, Mark Livolsi ; music, Marcelo Zarvos.
Julia Roberts, Owen Wilson, Jacob Tremblay, Izabela Vidovic, Mandy Patinkin, Daveed Diggs, Sonia Braga.
DVD; Region 1; 16x9 Widescreen 2.40:1 presentation; 5.1 Dolby digital.
Keywords: Self-acceptance -- Drama -- DVDs; Social acceptance -- Drama -- DVDs; Middle schools -- Drama -- DVDs; Families -- Drama -- DVDs; Craniofacial Abnormalities -- Drama -- DVDs; Feature films; Video recordings for the hearing impaired